Perbandingan Kandungan Selulosa dan Lignin dari Kayu Acacia crassicarpa dan Acacia mangium - Melysa Putri; Shalsyabila Poeni (REACTOR: Journal of Research on Chemistry and Engineering, 2020)
The development of the pulp & paper industries in Indonesia increase every year. To support the development of industries in Indonesia in order to be able to compete with similar industries from abroad, it is very important to pay attention to the quality of the paper produced. One way to determine the quality of the pulp & paper is by knowing the chemical composition and area where the wood grows. Important chemical compositions that can support the strength of wood and paper quality include cellulose and lignin. Therefore, this study was conducted to the levels of cellulose and lignin contained in Acacia crassicarpa wood from wetlands and Acacia mangium from dry land which is processed into pulp & paper with good quality. Determination of cellulose and lignin content in wood was carried out using the gravimetric method. Test results on Acacia crassicarpa wood species from wetlands obtained cellulose content of 55.48% and lignin 24.13%, while in Acacia mangium wood from dry land obtained cellulose content of 51.46% and lignin 27.66%. According to The National Indonesian Standards that levels of cellulose in two different fields are obtained according to the standards. So for the results of testing Acacia crassicarpa wood from wetlands has the highest levels of cellulose with low levels of lignin.